Towards Bureaucratic Reform to Achieve Good Governance - Agus Fatah Hidayat (Universitas Sultan Ageng Tirtayasa, 2022)
One of the promises of change through bureaucratic reform is the implementation of great services for the benefit of society, but disparities sometimes lead to conflicts in their execution. This took place in Tasikmalaya Regency, where, on the one hand, the bureaucracy is energetically adopting bureaucratic reform as a form of self-improvement, but, on the other hand, a decline in the culture of service and weak employee integrity are obstructing the bureaucracy's growth. The goal of this essay is to determine what factors help and what factors hinder the implementation of bureaucratic reform in the Tasikmalaya Regency Government, as well as what factors contribute to less-than-ideal evaluation results. In this study, we used qualitative research techniques. Observation, notes, and interviews were all parts of the data collection process. Collecting data, reducing data, presenting data, analyzing data, triangulating data, and generating conclusions are all data analysis techniques that can be used to determine the reliability of data and arrive at the truth. According to this paper's findings, the Tasikmalaya Regency government's bureaucratic reform has not moved significantly in a more optimal direction in its quest to accomplish good governance; normative difficulties pertaining to the quality and capacity of apparatus resources persist. When it comes to making significant changes and updates to the governance system, effective governance necessitates increased dedication and a mental shift on the part of leadership and all levels of employees.